IS AN ALBANIAN MAN’S BESA HIS BOND? - Fatma Shijaku (Proverbium)
“An Englishman’s word is his bond”. What about the Albanian concept of besa? Besa, regarded as the holiest word and a precious value in Albanian culture, is reflected in Albanian personal names, legends and ballads, customary laws, and the works of both English and Albanian writers such as Edith Durham and Ismail Kadare. It is also present in museums dedicated to the rescue of Jews during the Holocaust, in cultural and political events, and in media coverage, such as the BBC article “What can Albania teach us about trust?” Considered the cornerstone of the Albanian code of honour in past centuries and a defining virtue of Albanian identity, besa has generated a rich corpus of proverbs. This study explores proverbs about besa in the Albanian language, as depicted in Albanian written sources, primarily dictionaries such as “Fjalë të urta të popullit shqiptar” (“Wise sayings of Albanian people” by Jorgo Panajoti and Agron Xhagolli, 1983) and “Fjalor i Shqipes së Sotme” (Dictionary of Current Albanian Language, 2002). The aim is to portray the many nuances and attitudes encapsulated by besa in these proverbs. The discussion highlights the richness of Albanian proverbs about “trust, troth, the pledged word, honour, the solemn promise and bond”, i.e. besa, by examining their content and cultural significance.